TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENYIRAMAN AIR KERAS STUDI KASUS PUTUSAN PENGADILAN DENGAN (NOMOR PERKARA 372/PID.B/2020/PN JKT.UTR) (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Dousing hard water is a criminal act that can endanger an individual's life, hard water is a fairly concentrated acid solution, when hard water hits the skin it can cause severe pain, even skin burns, someone who is exposed to hard water will experience physical damage, even it can causing permanent injury. Criminal provisions for criminal acts or offenses for maltreatment themselves are included in the Criminal Code, namely in Articles 351 to 358 of the Criminal Code. The purpose of writing this thesis: first, to find out the basis for the judge's consideration in making a decision with case number 372 / Pid.B / 2020 / PN Jkt.Utr against the perpetrators of sprinkling hard water. Second, to find the ideal sanction against the perpetrators of sprinkling hard water in the criminal justice system in Indonesia. The author conducts normative juridical research or literature study in order to obtain secondary data through documentary studies by studying and analyzing a comparative descriptive of laws and regulations with theories that have a relationship to the problems studied. From the research results, there are two main points that can be concluded. First, the basis for the judge's decision in making a decision against the perpetrator of hard water sprinkling persecution with Decision Number 372 / Pid.B / 2020 / PN Jkt.Utr is that the judge only sees the actions committed by the perpetrator without seeing or considering the consequences of the actions of the perpetrators. the perpetrator. Second, the ideal sanction for the perpetrators of mistreatment of sprinkling hard water in the criminal justice system in Indonesia is that apart from seeing the actions committed by the perpetrators, they must also consider justice for victims who have been harmed, then looking at similar cases, the punishment should at least be imposed on the perpetrators 5 (five) years in prison or the equivalent of a similar case previously and added to pay for the cost of treatment for victims who certainly need intensive care in the hospital and after recovering mentally they must also be given treatment because the disability experienced by the victim is very likely to make the victim depressed and depression. The author's suggestion is that the judge in making a decision should look at similar cases, how similar cases are handled, how the decision is made which will be taken into consideration by the judge to decide the same case. In order to impose a sentence on a defendant of a criminal act of maltreatment, it should consider the consequences experienced by the victim, whether the victim is lightly injured, seriously injured or disabled, all of which must be taken into consideration by the judge in deciding a decision. The ideal sanction, according to the author, sees the consequences experienced by the victim, namely permanent disability so that the daily activities of the victim are interrupted and seen from the victim is a KPK investigator whose safety should be extra guarded instead of receiving this kind of abuse, the ideal punishment is at least a minimum of five years in prison, or at least similar to similar cases where there is no sentence under seven years in prison, so that justice can be obtained by the victim, give clear effects to the perpetrator and so that the same thing does not happen to anyone and fulfill community anxiety. Keywords: Juridical review - Crime - Flushing with hard water - Case Number 372 / Pid.B / 2020 / PN Jkt.Utr